Pengaruh Metode Take And Give Terhadap Hasil Belajar PAI Siswa Kelas VII SMPN 3 Sungai Pua - Ilfa Efani; Arifmiboy Arifmiboy; Hamdi Abdul Karim; Charles Charles (Badan Penerbit STIEPARI Press, 2023)
The background is that the learning outcomes of class VII students of PAI at SMPN 3 Sungai Pua are classified as low. The cause of the low student learning outcomes is due to the conventional methods used by educators so that students are not innovative and active in the learning process. Students only listen to the teacher in conveying the material without any response. That way the author applies the Take and Give method so that students can be active in receiving the knowledge that is entrusted. This research is an experimental research using a non-equivalent control group design. The aim is to see the impact of the Take and Give method on student learning outcomes. Its population is 83 people. Class VII.1 research sample as many as 30 students in class test. VII.2 27 students from the test class and 26 students from the control class VII.3. The hypothesis test used is the paired test and independent test, which are used to determine whether the hypothesis is rejected or accepted. The results of the study revealed that based on the acquisition of the t-test, a sig (2-tailed) value of 0.000 <0.000 was obtained at a significant level of 5% so that ha was accepted and ho was rejected. So it is proven that there is a significant influence of the Take And Give method on the learning outcomes of PAI students at SMPN 3 Sungai Pua.